Educational Supervision Patterns in Improving the Quality of Private High School Graduates - Ahmad, Rifai; Nasrul Syakur Chaniago (Journal of Educational Management Research, 2025)
The background of this study focuses on the importance of educational supervision in improving the quality of learning and graduates in secondary schools. An effective supervision system can play an important role in improving the quality of teaching and responsiveness to students' learning needs. This study aims to examine the pattern of educational supervision applied in private secondary schools, with a focus on collaboration between supervisors and teachers to improve the quality of learning. The approach used is qualitative research with a case study design. Data were collected through interviews with supervisors and teachers, direct observations in class, and analysis of documentation related to supervision activities. The results of the study indicate that supervision is carried out through classroom observations, weekly evaluations, and reflective discussions between supervisors and teachers. Follow-up to the results of supervision, such as improvement planning and implementation of remedial strategies, has proven effective in improving the quality of learning and student understanding. The implication of this study is the importance of a collaborative approach in supervision that allows teachers and supervisors to work together to improve teaching methods. This study contributes to the development of a collaboration-based educational supervision model. The limitations of this study lie in the limited scope of one school, so further research with a wider scope is needed to generalize these findings.